Chemistry NEET for everyone Part 1 - R. Sharma (Andover Cengage Learning India Pvt. Ltd., 2018)
Chemistry NEET for everyone: Part 1 aims to provide students with a comprehensive text that not only helps them build on their theory and principles but also helps them come face to face with situations involving applications of their learning. The learner friendly approach adopted in this book will help students learn faster and more easily owing to its efficient method of organizing theory and learning materials to maximize learning.